2021
DOI: 10.1021/acs.cgd.1c00506
|View full text |Cite
|
Sign up to set email alerts
|

A Hydrogen-Bonded Organic Framework Based on Pyrazinopyrazine

Abstract: Hydrogen-bonded organic frameworks (HOFs) composed of high-nitrogen-content π-conjugated molecules are expected to show multifunctionality. In this study, we studied on a HOF based on pyrazinopyrazine (PP), which is one of the simplest and the most essential structural motifs of high-nitrogen-content polycyclic aromatic hydrocarbons. We describe synthesis of a PPbased building block molecule with four carboxyphenyl groups (CP-PP), spectroscopic and electronic properties of CP-PP and its ester precursor, struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 41 publications
1
23
0
Order By: Relevance
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…Through the rational design of organic building blocks with geometric symmetry, planar molecules with diverse π-conjugated systems can coordinate to each other through intermolecular H-bonding interactions to form a single layer, and multiple layers pack together through strong π–π-stacking interactions to form a 3D framework with one-dimensional (1D) channels throughout the structure. HOFs that contain large, π-conjugated aromatic molecules as building blocks exhibit significantly enhanced thermal stabilities and increased chemical resistance to organic solvents and acidic or basic aqueous solutions due to the inert reactivity of the tectons (Figure ) (see refs , , , , , , , , , , , , , , , , , , , , , , , ). Several groups have independently demonstrated that HOFs with shape-fitted π–π-stacking interactions not only show type III stability upon desolvation but also become even more stable as the effective π–π-stacking areas become larger (Table ).…”
Section: Design Rules Of Stable Hofsmentioning
confidence: 99%
“…The 2D square lattice ( sql net) is the most common platform used for the construction of stable HOFs. For example, Liu and Cao et al isolated a crystalline PFC-1 based on 1,3,6,8-tetrakis­( p -benzoic acid)­pyrene (H 4 TBAPy) that comprises a large π-conjugated planar scaffold pyrene and four benzoic acid arms (Figure a) . In PFC-1, each H 4 TBAPy is connected by four adjacent ones by carboxyl dimers, forming 2D hydrogen-bonded layers with sql topology.…”
Section: Stability Enhancementmentioning
confidence: 99%
“…Removal of guest molecules from the pores of HOFs results in pore shrinkage and/or structural transitions of the framework associated with recombination or dissociation. [48][49][50][51] The molecular conformation, stacking manner, and hydrogen bonds of C1N4DBC-1 were perturbed, resulting in shrinkage of the pore aperture along the shorter direction. However, structurally hindered 1-naphthyl spacers as well as the shapefitted docking of DBC cores prevented a drastic transition that would have led to collapse of the framework into an amorphous state.…”
Section: Proposed Lattice Change In C1n4dbc-1mentioning
confidence: 99%